Sintering behavior and properties of reinforced hydroxyapatite/TCP biphasic bioceramics with ZnO-whiskers - (:unkn) unknown (SAGE PUBLICATIONS LTD, 2011)
Composite materials of hydroxyapatite/beta-tricalcium phosphate (HA/beta-TCP) biphasic bioceramics and ZnO whiskers, added in amounts up to 3 wt% to an HA/beta-TCP matrix, were prepared by sintering. The sintering behavior, the mechanical reinforcement (due to ZnO), and the mineralization ability of the resulting materials in simulated body fluid (SBF) were experimentally investigated. The experimental results showed that the densification and mechanical properties were improved with increasing amounts of ZnO. The presence of ZnO appeared to affect the proportion of HA/beta-TCP after sintering. Doping with a high amount of ZnO favored the dissolution of the materials in SBF.
Keywords: biphasic calcium phosphates; zinc oxide whiskers; mechanical properties; microstructure; biomineralization; CALCIUM-PHOSPHATE; MECHANICAL-PROPERTIES; IN-VITRO; VERSATILE MATERIAL; BIOACTIVE GLASS; ZINC PHOSPHATE; BONE-FORMATION; COMPOSITES; HYDROXYLAPATITE; IMPLANT